Functional tasks of elements of marketing and logistics management systems - Djurayev Bekzod Bekmatovich (THE INNOVATION ECONOMY, 2026)
This article examines the coordination of agricultural production, storage, and marketing processes, as well as the proper organization of trade flows, as one of the pressing issues of our time. The study offers scientifically sound proposals and recommendations on the current state of the marketing and logistics system in the agricultural sector, its development stages, and prospects for further improvement